Evaluation and Comparison of the Nutritional and Mineral Content of Milk Formula in the Saudi Arabia Market - Alfaris, Nora A.; Alothman, Zeid A.; Aldayel, Tahany S.; Wabaidur, Saikh M.; Altamimi, Jozaa Z. (Frontiers in Nutrition, 2022)
Background/Aim:As recommended by World Health Organization, breastfeeding is the best choice and safe for infants. The formula for infants plays an imperative role in the infant's diet and remains an excellent alternative for breast milk. The milk formula for most infants has been increasingly changed with various compositions to create a similar breast milk production. This study aims to analyze and determine the chemical composition of a few milk formulas available in the Saudi Arabian market. Materials and Methods: Thirty-five milk formula samples for infants of different age categories were collected from Riyadh city and analyzed for protein, fat, carbohydrates, lactose, total solids, total non-fat solids, calcium, iron, and zinc. Among batches collected, there were 15 branded products suitable for those of age 0-6 months, 5 for those of age 0-12 months, 4 for those of age 1-3 years, and 11 for those of age 6-12 months. Results: For the same age, milk formula sample parameters investigated varied significantly (P ≤ 0.05). A significant high protein value was 22.72% for a brand for infants with an age of 0-6 months, and a low one was 11.31% for a brand for those of age 0-12 months. Fat content was high in a brand (26.92%) for an infants of age 0-6 months and low in a brand (17.31%) for those aged 6-12 months. The high value of carbohydrates was found in a brand (60.64%) for those of age 0-6 months and low one (44.97%) in a brand for those of age 0-12 months. The total energy, lactose, total solids, total non-fat solids, and minerals (calcium, iron, zinc) were significantly (P ≤ 0.05) varied between milk formulas at the same age. Conclusion: There were significant variations between milk formulas of the same ages. According to age groups, some nutrients were not identical to the reference values for children's food.